2017
DOI: 10.21037/atm.2017.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Surgical prophylaxis with gentamicin and acute kidney injury: a systematic review and meta-analysis

Abstract: Background: Gentamicin has been increasingly used instead of cephalosporins for surgical prophylaxis in an attempt to reduce the rate of "Clostridium difficile" infection. There are limited data regarding nephrotoxicity related to gentamicin in these patients. Methods:We have conducted a systematic review and meta-analysis to evaluate the risk of acute kidney injury (AKI) in gentamicin-containing surgical prophylactic regimens, compared to regimens without gentamicin, in several types of surgery. Electronic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Gentamicin belongs to the aminoglycoside group; it is active against Gram negatives and the most common bacterial strains found in orthopedic surgeries or following open fractures, above all staphylococcus species. Although its efficacy is high, gentamicin is not commonly used for systemic antibiotic prophylaxis in orthopedic surgery as it has a small therapeutic index and serious dose-dependent side effects [ 31 ]. It has been shown that the amount of gentamicin released into circulation by coated nails does not reach systemic toxicity levels [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gentamicin belongs to the aminoglycoside group; it is active against Gram negatives and the most common bacterial strains found in orthopedic surgeries or following open fractures, above all staphylococcus species. Although its efficacy is high, gentamicin is not commonly used for systemic antibiotic prophylaxis in orthopedic surgery as it has a small therapeutic index and serious dose-dependent side effects [ 31 ]. It has been shown that the amount of gentamicin released into circulation by coated nails does not reach systemic toxicity levels [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this medication is particularly dangerous if it is erroneously administered intravenously to a patient undergoing kidney transplantation because it can damage the newly transplanted kidney. Prophylactic gentamicin has recently been shown to be a significant cause of acute kidney injury in orthopedic surgery 5,6 . Inadvertent IV administration of gentamicin therefore constitutes a significant unnecessary risk for the transplanted kidney.…”
Section: Discussionmentioning
confidence: 99%
“…AKI occurred despite the reduced gentamicin dose of 2-3 mg/kg ideal body weight (or adjusted body weight if obese). Studies suggest that the majority of gentamicin-associated AKIs are transient and many patients, such as Case 3 , may ultimately return to baseline renal function [4]. However, transient AKI can worsen baseline renal function, as seen in Cases 1 and 2, and even significantly increase the risk of future end-stage renal disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, the study was limited by the lack of any postoperative measures of nephrotoxicity and only evaluated rates of readmission for AKI. Interestingly, the majority of gentamicin-associated cases of AKI are subclinical stage-1 insults, making readmission rates an inadequate outcome measure [4]. In addition, there are no specific recommendations regarding dose adjustment for patients with preexisting conditions such as chronic kidney disease (CKD) or diabetes mellitus (DM) which are highly prevalent in individuals with medication-refractory erectile dysfunction.…”
Section: Introductionmentioning
confidence: 99%